2018
DOI: 10.1152/advan.00174.2017
|View full text |Cite
|
Sign up to set email alerts
|

Involving a real patient in the design and implementation of case-based learning to engage learners

Abstract: Real patients offer unique opportunities to develop authentic, engaging, and transformative learning experiences for students. Patients are widely employed to teach clinical and interpersonal skills in the clerkship phase of their medical education (M3-M4), but have not been extensively included in the preclinical curriculum (M1-M2) when students are focused on acquiring foundational biomedical science knowledge. To maximize learning and help students connect foundational and clinical science concepts to real-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 31 publications
1
49
0
Order By: Relevance
“…The case-based teaching method is beginning to be explored domestically after the 1990s and is being gradually applied to multiple subject fields of education. Over the past decade, the use of CBL in medical education has increased exponentially (Lee et al 2014;Dickinson et al 2018). The application of case teaching method to the teaching and research of oncology is less, and it is mostly a pure theoretical review.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The case-based teaching method is beginning to be explored domestically after the 1990s and is being gradually applied to multiple subject fields of education. Over the past decade, the use of CBL in medical education has increased exponentially (Lee et al 2014;Dickinson et al 2018). The application of case teaching method to the teaching and research of oncology is less, and it is mostly a pure theoretical review.…”
Section: Discussionmentioning
confidence: 99%
“…This makes students lose motivation, lack self-study ability, and the combination of curriculum and clinical work is not close enough to train students' clinical thinking. The traditional teaching method has been shown to be less effective than other teaching strategies in practical application and critical thinking abilities (Ilkiw et al 2017;Dickinson et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Case-based and problem-based learning were also proposed. However, despite the advantages of a patient-centred approach to learning physiology [58,59], we decided on a teaching format that used a presentation focused on one specific topic to ensure a systematic curriculum independent of actual patients.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid development of health care needs and the relative lag in comprehensive teaching modes have created higher requirements for the medical education system and greater challenges for medical educators. Previous studies have revealed the limitations of the traditional lecture-based learning (LBL) model with respect to problem-solving, collaborative learning, and lifelong learning strategies and have noted side effects such as decreased motivation and poor self-study, practical application and critical thinking abilities [7][8][9].…”
Section: Introductionmentioning
confidence: 99%